The role of extracellular vesicles in vascular calcification in chronic kidney disease - Zhao, Huan; Liu, Haojie; Liu, Yueming; Jin, Juan; He, Qiang; Lin, Bo (Frontiers in Medicine, 2022)
Widespread vascular calcification in patients with chronic kidney disease is the pathological basis for the development of cardiovascular disease, and vascular calcification has been identified as an independent risk factor for increased cardiovascular mortality in cases of chronic kidney disease. While vascular calcification was earlier thought to be a passive deposition process following calcium and phosphorus supersaturation, recent studies have suggested that it is an active, modifiable, biological process similar to bone development. The involvement of extracellular vesicles in the process of vascular calcification has been reported as an important transporter of material transport and intercellular communication. This paper reviews the mechanism of the role of extracellular vesicles, especially exosomes, in vascular calcification and the regulation of vascular calcification by stem cell-derived extracellular vesicles, and discusses the possible and promising application of related therapeutic targets in the clinical setting.